The phase transitions character and microscopic models for Sn₂P₂S(Se)₆ ferroelectrics - Vysochanskii, Yu.; Drobnich, A. (Condensed Matter Physics, 2002)
The paper considers an example of concrete objects, i.e. ferroelectrics of
Sn₂P₂S₆ family, for which, according to general estimations, a correlation
between the shape of a phase diagram (the presence of a Lifshitz point
and of a tricritical point) and a crossover “displacive to order/disorder” is
observed. Simulations by means of microscopic models, which most adequately
represent a dipole ordering in these crystals, are analyzed. A dimension
dependence of a ferroelectric phase transition temperature for
microcrystals of Sn₂P₂S₆ compound is considered. В статті досліджена кореляція між особливостями фазової діаграми (наявність на діаграмі точки Ліфшиця та трикритичної точки) та кросовером характеру фазових переходів від типу зміщення до типу лад-безлад на прикладі конкретних об’єктів, а саме сегнетоелектриків родини Sn₂P₂S₆. Аналізуються результати комп’ютерного моделювання з використанням мікроскопічних моделей, що найбільш адекватно відображають дипольне впорядкування в цих кристалах. Розглядається ефект розмірної залежності температури сег-нетоелектричного фазового переходу для мікрокристалів сполуки Sn₂P₂S₆.